2023
DOI: 10.1615/intjmedmushrooms.2022047222
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Potential of the Insoluble Extracted Fibers Isolated from the Fomes fomentarius (Agaricomycetes) Fruiting Bodies: A Review

Abstract: The tough, hoof-shaped fruiting bodies of the tinder conk mushroom, <i>Fomes fomentarius</i> (L.) Fr. (Polyporaceae, Agaricomycetes), were traditionally used all over the world as tinder to start fire, for ritual purposes, to make artworks like clothing, frames, ornaments, and also to cure various human diseases (wounds, gastro-intestinal disorders, liver-related problems, inflammations, various cancers, etc.). The first wave of scientific interest in <i>F. fomentarius</i> in Europe dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Clinical trials on patients with wounds, burns, and trophic ulcers indicated that topical application of the fibers resulted in stopping the bleeding, reducing pain, and preventing inflammation and suppuration [123]. Furthermore, F. fomentarius has diverse medicinal applications including anti-cancer [125,133], anti-diabetes [129], antimicrobial [128,131], anti-inflammatory [126], and antioxidant activities [132,134,135].…”
Section: Distribution Of Medicinal Basidiomycetes By Areas Of Uzbekistanmentioning
confidence: 99%
“…Clinical trials on patients with wounds, burns, and trophic ulcers indicated that topical application of the fibers resulted in stopping the bleeding, reducing pain, and preventing inflammation and suppuration [123]. Furthermore, F. fomentarius has diverse medicinal applications including anti-cancer [125,133], anti-diabetes [129], antimicrobial [128,131], anti-inflammatory [126], and antioxidant activities [132,134,135].…”
Section: Distribution Of Medicinal Basidiomycetes By Areas Of Uzbekistanmentioning
confidence: 99%